Happiness and wisdom : Augustine's early theology of education - Topping, Ryan N. S. (Ryan Nathan Scott), 1977- (Catholic University of America Press, 2012)
"Immediately after his baptism Augustine set out to produce a Christianized version of the ancient liberal arts curriculum. By an ordered sequence of contemplation, moving from linguistic to mathematically based disciplines, Augustine suggested that study in the liberal arts could render the mind and heart docile before God. Though Augustine later would shift his focus more directly toward biblical study, his early reflections on secular learning remain an attractive and powerful model for Christian thinking about the arts. Happiness and Wisdom contributes to ongoing debates about the nature of Augustine's early development, and argues that Augustine's vision of the soul's ascent through the liberal arts is an attractive and basically coherent view of learning, which, while not wholly novel, surpasses both classical and earlier patristic renderings of the aims of education. Ryan N.S. Topping begins by embedding Augustine's educational works within the historical and philosophical context of Christian and pagan late antiquity. He then shows how Augustine's writings on education, far from being irrelevant to the trajectory of his mature thought, provide a key to interpreting many of his other explorations in ethics and epistemology. Augustine's Christianized liberal arts curriculum is vindicated as an outgrowth of his moral theology, an expression of his abiding conviction that happiness is the end of human aspiration, and that -- against both Ciceronian skepticism and Manichean dualism -- the created order speaks to men of the mind of God."--Publisher's description